PENGARUH PENDIDIKAN DAN JENIS KELAMIN TERHADAP PENYERAPAN TENAGA KERJA PADA SEKTOR AKOMODASI HOTEL DAERAH PAMEKASAN - Rukmiadim, Dwi Masitoh; Wispandono, R.M. Moch. (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Tourism is one of the sectors that support the economy, one of the sectors that support tourism is hotel accommodation. With the existence of hotel accommodation, it does not rule out the possibility of job opportunities for the community. Things that are often considered in recruiting employees are education and gender factors. This study analyzes how education and gender factors affect employment in Pamekasan Hotels. This type of research is quantitative research with Non Probability Sampling method using quota sampling technique. The data obtained was tested using SPSS. The test carried out is multiple linear regression, where before conducting the test the classical assumption test is carried out. The results of this study indicate that education and sex simultaneously have a positive and significant effect on labor absorption. Education and sex have an influence of 48% and 52% is influenced by other variables outside these variables.